Light Navigation Around the Republic of Kalmikia, RUSSIA - Maltseva, Anna; Bainkharaeva, Kermen; Pinaeva, Aleksandra; Vik, Michal (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
Kalmykia is a unique region in the Russian Federation as its identity dramatically different from other regions of the European part of Russia. It is an intercultural westernmost part of Russia, which professes Buddhism; its traditions are tightly connected with its religion creating a nonrecurring environment. "Navigation system of Kalmykia, Russia", tries to solve an existing problem of promoting the cultural heritage of the Republic both within Russia and abroad. One of the goals of this project is to attract people to Kalmykia, introduce them to the Buddhist culture and boost the development of the whole region, as Kalmykia is not yet a very well known place, despite its outstanding beauty. Based on a thorough research of Buddhist philosophy, traditions and culture the concept of a special navigation system was developed. This system crosslinks traditions, legends and beliefs with modern technologies. The concept of a tourist navigation system in the form of a network of laser beams with the possible application of special textiles and reflective elements was proposed. This connects the design with modern technologies and improves communication between cultural researchers and technical developers. Tourists will find a special light net with beacons near every place of importance. Furthermore, this solution resulted in the creation of a website.
Světelná navigace v republice Kalmikia, Rusko
Keywords: light; integration; Buddhism philosophy; concept of design